Towards a theory of the grotesque in the Latin American indigenist narrative - Lopez-Saravia, Fernando J. (2022)
This scientific research article seeks to verify if the resources of grotesque aesthetics enrich the analysis of the indigenist narrative with the purpose that these novels are no longer only valued as vehicles of denunciation, as they are usually catalogued, but also as artistic products. Based on an analysis of different theorists of the grotesque, this research proposed categories of analysis, such as narrative intrusions, animalization, the mixture of the heterogeneous, the disruption of reality, caricatures, allegories, and the utopian function. The used methods were the narratology, rhetoric and hermeneutics, procedures through which it was sought to demonstrate the hypothesis, taking as a sample, fragments of the novels Huasipungo by Jorge Icaza and El tungsteno by César Vallejo. The main result obtained shows that, in its essence, the grotesque aesthetic is very related to Latin American culture. Therefore, it was concluded that an analysis of the grotesque aesthetic turns out to be not only pertinent, but also beneficial for the indigenist narrative, since it not only starts lines of research that were not well developed, but also allows the precise determination of the purpose of the authors.